IPTEKS PENGENDALIAN INTERN TERHADAP ASET TETAP DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C / KPPBC TMP C BITUNG - Mamentu, Timons P. M.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2018)
This article discusses about the implementation of IPTEKS of internal control on fixed assets. The method used in this article is how to implement the internal control structure. In order to implement the internal control well, an organization must fulfil the 5 aspect in internal control, which are: environment control, risk grading, information and communication, supervision, and activity control. It is suggested that Office of Customs and Excise Branch Bitung to keep maintaining the applied internal control..Keywords: internal control, service, fixed assets